Reports - Vasiuk, Volodymyr; Zinchenko, Anatoliy; Horpenyuk, Oleg; Klepach, Mykola; Smolynskyy, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Report of the societies and associations of orthopedic trauma of Ukraine.